An Approach to Knee Osteoarthrosis as a Significant Pathology in the General and Military Population (London Journal of Medical and Health Research, 2024)
Osteoarthrosis (OA) is one of the most common joint diseases. It affects a significant portion of the population, among which the military, who suffer mainly from post-traumatic knee osteoarthrosis. Being aware of this relationship fosters early preventive and/or protective behaviours among health personnel and allows them to proceed with timely therapeutic measures.
Keywords: enzymes.; Burns; hypertrophic scars; skin grafts; collagenase; recombinant.; Total ischemic time; Primary PCI (pPCI); prognostic implications.; Chemotherapy; Cancer therapy; differentiation therapy; immunotherapy; CDA; CSCs; DIs; DHIs; PSCs; Wound healing.; Osteoarthrosis; joint degeneration; mechanical disorders; military pathology.